The fluoride concentration in ground potable water samples of some regions of LIBYA - Hasan, Hamad . M.I. (Al-Mukhtar Journal of Sciences, 2010)
Eighteen potable drinking water samples were collected from ground water sources lie at the eastern north side of Libya during (2007). The fluoride ions were analyzed on the studied samples at the first time in the investigated area. The obtained data showed that the fluoride concentrations ranged between ( 0.10-1.4 mgŁ). The results of fluoride ions were compared with the standard limits and with the fluoride levels of some international Arabic water sources . The results obtained showed that the concentrations of fluoride ions in the studied regions are in the safety range except for that taken from El- mekhaily area.